Incidence of COVID-19-associated mucormycosis in COVID-19 patients after discharge from the COVID-19 hospital - Aayush Kulshrestha; Richa Aggarwal; Parul Kodan; Yudhyavir Singh; Rakesh Kumar; Kapil D Soni; Purva Mathur (Wolters Kluwer Medknow Publications, 2023)
Background: There are studies available on the prevalence of coronavirus disease 2019 (COVID-19)-associated mucormycosis (CAM) in hospitalized patients but not on the incidence of CAM in post-discharge patients. The aim of our study was to find the incidence of CAM in the patients discharged from a COVID hospital. Material and Methods: Adult patients with COVID discharged between March 1, 2021 and June 30, 2021 were contacted and enquired about sign and symptoms of CAM. Data of all included patients were collected from electronic records. Results: A total of 850 patients responded, among which 59.4% were males, 66.4% patients had co-morbidities, and 24.2% had diabetes mellitus. Around 73% of patients had moderate to severe disease and were given steroids; however, only two patients developed CAM post discharge. Conclusion: The incidence of CAM post discharge was low in our study, which could be attributed to protocolized therapy and intensive monitoring.